Establishment of an ultrasensitive indirect competitive time-resolved fluoroimmunoassay for vancomycin determination. Issue 1 (1st January 2019) - Xu, Chongxin; Han, Qi; Dong, Sa; Liu, Xiaoqin; Liu, Xianjin
ABSTRACT: Vancomycin (Van) is a common antibiotic that pollutes food, feed and ecological environment. In the present study, an anti-Van polyclonal antibodies (pAbs) and Eu 3+ -labeled goat anti-rabbit IgG monoclonal antibody based indirect competitive time-resolved fluoroimmunoassay (IC-TRFIA) was established for ultrasensitive determination of Van, and its half-maximum inhibition concentrations (IC50 ) was 13.74 ng/L and the limit of detection (LOD) was 1.07 ng/L. The IC-TRFIA showed strong cross-reactivity (CRs) of 36.2% for norvancomycin, and less than 0.1% for polymyxin B, kanamycin and ampicillin. It was found that the IC-TRFIA for Van spiked in different milk powder samples determination were with good accuracy, stability and repeatability, and its recoveries are 83.0–97.9%, also with its coefficient of variations (CVs) are 3.0–12.9% in intra-assay and inter-assay. The results showed that the established IC-TRFIA was promising for ultrasensitive determination of Van in food samples. Highlights Prepared high-quality Van-KLH/BSA conjugates. Obtained high activity and purify anti-Van polyclonal antibodies. Prepared high-quality Eu 3+ -labelled goat anti-rabbit IgG monoclonal antibody. Firstly established an IC-TRFIA for Van based on the anti-Van polyclonal antibodies and Eu 3+ -labelled goat anti-rabbit IgG monoclonal antibody. The IC-TRFIA can be used for ultrasensitive determination of Van in milk powder samples. GRAPHICAL ABSTRACT: